Analisis Ratio Indeks Maqashid Syariah pada Bank Pembiayaan Rakyat Syariah, Unit Usaha Syariah dan Bank Umum Syariah Periode 2016-2020 - Anwar Sholihin; Feny Lestari; Sinky Adella (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to discuss the comparison of the Islamic Maqashid Index (IMS) assessment at Islamic Commercial Banks (BUS), Sharia Business Units (UUS) and Sharia People's Financing Banks (BPRS) in Indonesia in 2016-2020. interpreted and analyzed the causative factors. This paper uses a descriptive method with a quantitative approach with data sources taken from Islamic banking financial ratios at https://www.ojk.go.id. The results of the study show that the comparison of Islamic maqashid index (IMS) numbers at Islamic Commercial Banks (BUS), Sharia Business Units (UUS) and Sharia People's Financing Banks (BPRS) in Indonesia fluctuates. This indicates that BUS, UUS and BPRS have not been maximal in carrying out the sharia objectives of Islamic banking itself. The factors that cause this to happen are a decrease in the budget for education, training, research and publications, a decrease in the amount of profitability, the disbursement of zakat has not been implemented and a decrease in investment in the real sector.